Social Innovation for the Welfare of the Community - Varga, Krisztina (International Journal of Engineering and Management Sciences, 2020)
The aim of the study is to highlight the focal points that are potentially activating factors in social innovation efforts in the most disadvantaged areas. The study examines certain social initiatives in the Nyírbátor district, with particular emphasis on the efforts promoting community welfare. The study primarily presents the results of qualitative interviews as part of a doctoral research. The examined cases play an important role in the management of the unfavourable processes in the region, and their adaptation as good practice can support the catching-up process. The study identifies the main groups of aspects that, in addition to structuring the case descriptions, also facilitate comparability of good practice. Documentation based on defined criteria supports the adaptation process, which is critical to the successful implementation of social innovation efforts.